Organizational culture, human resource practices and employee engagement among academic staff of Universiti Utara Malaysia - Nor Arpizah, Atan (2016)
The purpose of this study is to examine whether organizational culture and human resource practices influence employee engagement among academic staff in Universiti Utara Malaysia (UUM). Two dimension of organizational culture namely perceived organizational support (POS) and stability were used. Whereas three dimensions of HRM practices namely, salary, training and career development will be the focus of this study to determine the influence on employee engagement. Primarily, this is a quantitative study developed research instruments the experts and original researcher already proven in terms of reliability and validity on organizational culture and human resource practices. A total of 63 items were used in the questionnaire to examine all the variables illustrated in the theoretical framework. Data was collected through the self-administered by sending questionnaires to 320 academic staff in UUM. A total of 200 academic staff (62.5%) had duly completed and returned the forms. Pearson correlation and linear regression were used to achieve the objectives of the study. Mean analysis shows that organizational culture and human resource practices influence employee engagement among academic staff in UUM. The result of the Pearson correlation analysis shows that among all five independent variables, training in human resource practices is found to be the most significant variable in influence the employee engagement among academic staff of UUM.